2021
DOI: 10.3390/ma14071590
|View full text |Cite
|
Sign up to set email alerts
|

Titanium and Protein Adsorption: An Overview of Mechanisms and Effects of Surface Features

Abstract: Titanium and its alloys, specially Ti6Al4V, are among the most employed materials in orthopedic and dental implants. Cells response and osseointegration of implant devices are strongly dependent on the body–biomaterial interface zone. This interface is mainly defined by proteins: They adsorb immediately after implantation from blood and biological fluids, forming a layer on implant surfaces. Therefore, it is of utmost importance to understand which features of biomaterials surfaces influence formation of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
87
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 242 publications
(224 reference statements)
2
87
0
3
Order By: Relevance
“…From the zeta potential values (see Table 2 ), it can be concluded that transformation of TiO 2 surface charge from positive to negative after annealing increased the adsorption abilities of the tested samples. The negatively charged semiconductor surface has a higher potential of contact with the positively charged methylene blue molecules, due to the attractive electrostatic interactions [ 77 , 78 , 79 ]. Calcined APTES/TiO 2 nanomaterials showed clearly dissimilar adsorption degrees of the methylene blue compound; although, they demonstrated similar zeta potential values (i.e., 19% for TiO 2 -4 h-180 °C-500 mM-Ar-1000 °C but 75% of adsorbed dye for TiO 2 -4 h-180 °C-500 mM-Ar-800 °C).…”
Section: Resultsmentioning
confidence: 99%
“…From the zeta potential values (see Table 2 ), it can be concluded that transformation of TiO 2 surface charge from positive to negative after annealing increased the adsorption abilities of the tested samples. The negatively charged semiconductor surface has a higher potential of contact with the positively charged methylene blue molecules, due to the attractive electrostatic interactions [ 77 , 78 , 79 ]. Calcined APTES/TiO 2 nanomaterials showed clearly dissimilar adsorption degrees of the methylene blue compound; although, they demonstrated similar zeta potential values (i.e., 19% for TiO 2 -4 h-180 °C-500 mM-Ar-1000 °C but 75% of adsorbed dye for TiO 2 -4 h-180 °C-500 mM-Ar-800 °C).…”
Section: Resultsmentioning
confidence: 99%
“…We showed the localization of In-β4, an epithelial cell-specific adhesion molecule, and vinculin, an adhesion-related molecule in fibroblasts, which indicate the cellular attachment to the materials. In addition, well developed actin filament, a fundamental cytoskeleton component involving cell locomotion and proliferation [23], was observed. These results indicate that the soft tissue cells can attach and express biological functions on the materials.…”
Section: Discussionmentioning
confidence: 99%
“…42 Accordingly, enhanced protein adsorption was observed on the superhydrophilic nanotextured surfaces, correlating with literature reports. 43 This in turn can increase cell proliferation and promote better cellular response in vivo .…”
Section: Resultsmentioning
confidence: 99%